PENGARUH PENGETAHUAN PAJAK, PENYELEWENGAN PAJAK, PERSEPSI KINERJA PELAYANAN PERPAJAKAN, DAN KESADARAN PAJAK TERHADAP MOTIVASI KEWAJIBAN PERPAJAKAN - Ayuning Prawesti, 09.05.52.0136 (Students Journal of Accounting and Banking, 2013)
This study aimed to examine the effect of the knowledge of the taxpayer, tax fraud, the perception of the performance of the taxpayer, and the taxpayer awareness of the motivation taxpayers in meeting tax obligations.The research was conducted in Semarang Candisari Pratama Tax Office. The data was collected by means of questionnaires and interviews spread directly by the respondent that the taxpayer peribadi who performs with a sample of 100 respondents. And data used are primary data.This study uses multiple regression analysis to data analysis. Results of the study show knowledge taxpayers, tax fraud, the perception of performance, and the effect on the taxpayer awareness motivation taxpayers in meeting tax obligations.Keywords: knowledge, tax fraud, perceptions performance tax, tax awareness.